Chronic obstructive pulmonary disease Introduction. Issue 8 (1st August 2002) - Lomas, D A
Abstract : A series of review articles on chronic obstructive pulmonary disease beginning in this issue of Thorax will consider many of the basic science and clinical aspects and provide the clinical scientist and practising physician with an up to date understanding of this common and distressing lung disease.